2014
DOI: 10.3233/jad-140237
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the AMPK/Sirt1 Axis During Neuronal Infection by Herpes Simplex Virus Type 1

Abstract: Currently, it is unclear whether a neuron that undergoes viral reactivation and produces infectious particles survives and resumes latency or is killed, which is intriguing even if still unanswered. Previous reports have shown that herpes simplex virus type 1 (HSV-1) inhibits apoptosis during early infection, but is pro-apoptotic during productive infection. Taking in consideration that the stress sensors AMPK and Sirt1 are involved in neuronal survival and neuroprotection, we hypothesized that HSV-1 could act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Indirect immunofluorescence staining of fixed and permeabilized neuronal cells was performed as described (Martin et al, 2014b). Briefly, after fixation and permeabilization, cells were incubated with the corresponding primary antibodies diluted in PBS.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect immunofluorescence staining of fixed and permeabilized neuronal cells was performed as described (Martin et al, 2014b). Briefly, after fixation and permeabilization, cells were incubated with the corresponding primary antibodies diluted in PBS.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Recently, we showed that HSV-1 modulates the AMPK/Sirt1 axis during the course of neuronal infection (Martin et al, 2014b). In fact, during early infection (2 hpi) activated AMPK (p-AMPK) was down-regulated by the virus, possibly to favor viral protein translation, since p-AMPK inhibits mTORC1 pathway which is critical for the maintenance of cap-dependent translation (Shaw, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The roles of AMPK in the infection and replication of two members of herpesviruses, herpes simplex virus 1 (HSV-1) and human cytomegalovirus (HCMV), have been examined; however, the interactions of these viruses with the AMPK pathway appear to be complex (16)(17)(18)(19). At the early stage of infection (2 h postinfection), the AMPK activity was inhibited by HSV-1 infection; however, it gradually recovered as the infection progressed.…”
mentioning
confidence: 99%
“…At the early stage of infection (2 h postinfection), the AMPK activity was inhibited by HSV-1 infection; however, it gradually recovered as the infection progressed. AMPK agonist inhibited HSV-1 gene expression and viral production (17,19). Interestingly, both AMPK agonist and inhibitor impaired HCMV replication, suggesting that fine-tuning of AMPK activity might be essential for optimal HCMV replication (16,18).…”
mentioning
confidence: 99%
“…In addition to Us3, which acts downstream of Akt to activate mTORC1, the UL46-encoded gene product VP11/12 interacts with the phosphatidylinositol 3-kinase (PI3K) regulatory subunit p85 to stimulate Akt (22). While AMPK activation reportedly only modestly reduces virus replication in neurons, the capacity of HSV-1-encoded function(s) to antagonize AMPK activity, the identity of the function(s), and the mechanisms of action remain undefined (23,24).…”
mentioning
confidence: 99%